2019
DOI: 10.1155/2019/5256460
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Serum Bilirubin and Inflammatory Bowel Disease

Abstract: The associations between serum total bilirubin (sTB) levels, inflammatory marker levels, and disease activity are not well understood in patients with inflammatory bowel disease (IBD). The present study investigated the association between sTB levels and disease activity in patients with IBD. We conducted a retrospective study with a total of 242 consecutive patients with Crohn’s disease (CD) and 211 consecutive patients with ulcerative colitis (UC). The Crohn’s Disease Activity Index (CDAI) score was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 30 publications
7
30
0
Order By: Relevance
“…According to Fan et al [40], the increase in the concentration of cholesterol in rodents is a response to the production of inflammatory cytokines (mainly TNF-α and IL-1). Bilirubin is an endogenous antioxidant which promotes lipid peroxidation prevention [41]. Inoguchiet et al [42] reported that bilirubin plays a protective role against chronic inflammation.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…According to Fan et al [40], the increase in the concentration of cholesterol in rodents is a response to the production of inflammatory cytokines (mainly TNF-α and IL-1). Bilirubin is an endogenous antioxidant which promotes lipid peroxidation prevention [41]. Inoguchiet et al [42] reported that bilirubin plays a protective role against chronic inflammation.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC), is an idiopathic disease involving chronic inflammation of the gastrointestinal tract [1]. Although the pathogenesis of IBD has not yet been elucidated, most researchers currently believe that it is due to the interaction of genetic susceptibility, environmental factors, microbial flora imbalance, and immune disorders [2].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that bilirubin has an anti-in ammatory effect. C-reactive protein (CRP) is a marker of chronic in ammation; several studies have shown that serum bilirubin levels are negatively correlated with CRP levels [23,24]. Bilirubin can also inhibit the overexpression of vascular adhesion molecules induced by the in ammatory cytokine TNF-α [25].…”
Section: Discussionmentioning
confidence: 99%